Utilization of non-edible bio-feedstock Pongamia Pinnata-diethyl ether ternary fuel blend supplemented with graphene oxide nanoparticles on CRDi engine characteristics - Soudagar M.E.M.; Kiong T.S.; Ramesh S.; Ghazali N.N.N.; Kalam M.A.; Mujtaba M.A.; Venu H.; Nur-E-Alam M.; Ali H.M. (Springer Science and Business Media B.V., 2025)
This research addresses the challenges of emission reduction and fuel consumption in engines by investigating modifications in fuel properties using graphene oxide (GO) nanoparticles and diethyl ether as oxygenated additives. Characterization tests were conducted to determine the size, energy, and content of graphene and oxygen molecules in synthesized GO nanoparticles. Pongamia Pinnata Oil Methyl Ester (POME) was prepared through a transesterification process and blended with diesel to obtain a B20 blend. This POME (B20) was further mixed with GO nanoparticles at 40, 80, and 100mg L-1 concentrations and supplemented with 3vol% of diethyl ether. The blending process involved stirring, bath sonication, and probe sonication. A Common Rail Direct Injection diesel engine was employed with a toroidal combustion chamber and a 7-hole fuel injector nozzle. The engine maintained a steady speed of 1800rpm, an injection timing set at 23bTDC, and a fixed compression ratio of 18.5 while operating under five different loads. At maximum loading conditions, the addition of 100ppm GO nanoparticles and 5vol% of Diethyl ether resulted in a 19.7% enhancement in Brake Thermal Efficiency (BTE) and a 10.71% reduction in Brake Specific Fuel Consumption. Furthermore, there was a significant reduction observed in CO, HC, and smoke emissions by 47.9%, 70.3%, and 23.8%, respectively. The addition of these fuel additives increased combustion characteristics such as Heat Release Rate, Cumulative Heat Release Rate, peak pressure, and in-cylinder pressure, while concurrently decreasing the Ignition Delay period and Exhaust Gas Temperature. ? Akadmiai Kiad, Budapest, Hungary 2024. corrected publication 2024.